A validation exercise of the precipitation-runoff expolinear model using a rain simulator. - Paz Pellat, Fernando; López Bautista, Eliezer; Marín Sosa, Ma. Isabel (REVISTA TERRA LATINOAMERICANA, 2017)
The need to develop simplified, operational and coherent hydrological models, particularly regarding the rainfall-runoff relationship, is still one of the great challenges in this field of science. Many simple models, such as the curve number method or CN, have been proposed, but their theoretical bases have no hydrological fundaments. The advantage of the CN method is that only one parameter (CN) is required and this makes it very attractive for applications. Thus, in this paper the basis of the CN method is analyzed in terms of rates of change and the limits of applicability. The results show that these simplified attempts are limited. On the other hand, the expo-linear model of Paz (2013) is flexible in empirical terms. The theoretical basis of this model is discussed in terms of variable area hydrology using a general format to make its use solid. The model is applied to an experiment with a rainfall simulator in runoff lots with diverse types of soils and grass covers. The results show a good experimental f it to data, particularly in terms of the parameterization of the expo-linear model in a way analogous to the CN method. Thus, from these developments, we present an estimation scheme of parameters of the expo-linear model that can be used as a CN method equivalent because of its simplicity of having only one free parameter.